On an IP-centric optical control plane. - Xin, Chunsheng (IEEE Communications magazine)
This article presents an experimental study on adopting and integrating the existing IP protocols and mechanisms into an optical network control plane. Although there has been much research effort on the conceptual and functional requirements for the control of optical networks, this article focuses on the design and implementation of an optical control plane. The proposed control plane implements the key functions such as routing, signaling, protection/restoration, and quality of service